CONVENTIONAL AND UNCONVENTIONAL IN MILITARY ACTIONS - Teodor FRUNZETI (Annals: Series on Military Sciences, 2014)
The end of the Cold War, the accelerated globalization and the rapid development of means of warfare have brought about a new physiognomy of military actions, which in addition to conventional and unconventional warfare, now include military actions other than war. In this context, the present article seeks to answer the question “Is the conventional/unconventional dichotomy real in terms of contemporary military actions or the elements of each dimension overlap successfully in achieving the ultimate goal?”